The Electric Field and its Strength - Sh.Sh. Abdullayev (Genius Journals, 2022)
In this article, the electric field strength is explained in detail through the Gauss theorem and other examples.
Keywords: Gauss theorem; Coulomb's law; electric charge; positive charge